Manajemen Lembaga Sertifikasi Profesi LSP P1 dalam Menyiapkan Lulusan di SMK Kabupaten Kutai Timur - Hariyanti, Titik; Ilma, Okta Usrifatin; Sianturi, Herpina; Warman, Warman (Jurnal Indragiri Penelitian Multidisiplin, 2025)
Technological developments in the industrial era 4.0 have brought significant changes to vocational education policies, especially in preparing vocational high school graduates quickly and accurately. Industry 4.0 has influenced various aspects of life and work today, so that vocational education in vocational high schools has an important responsibility in equipping the younger generation to face the challenges of an increasingly complex and dynamic world of work. According to the official website of the Directorate General of Vocational Education (Ditjen Pendidikan Vokasi), the quality of vocational high school graduates can be measured by their contribution to society, which includes the percentage of graduates who work, continue their education, or become entrepreneurs (BMW). Alumni tracing, or tracer study, is carried out to collect feedback from graduates and the industrial world. This information becomes evaluation material in an effort to improve the quality of vocational education in vocational high schools. The Professional Certification Institute (LSP) P1 is an institution that plays a role in providing professional certification to prospective novice workers who do not yet have adequate work experience or skills in a particular field. LSP P1 can be in the form of an educational institution, such as a vocational high school or university. Management, as a process involving planning, organizing, supervising, and controlling resources, aims to achieve targets effectively and efficiently. This process involves the role of leaders, resource management (human, material, time, and financial), and the implementation of appropriate strategies. In the context of LSP P1, the implementation of planned and mature management is very necessary to ensure that SMK graduates have high competence and competitiveness in the world of work.